Metastatic Crohn Disease: A Clinicohistological Appraisal From a Tertiary Care Center in India. (July 2020) - Chatterjee, Debajyoti; Bhattacharjee, Rajsmita; Khullar, Geeti; Kumaran, Sendhil; De, Dipankar; Saikia, Uma N.; Radotra, Bishan D.
Abstract : Background: Granulomatous dermatitis due to noncontiguous involvement of Crohn disease (CD) of the gut has been described as metastatic CD (MCD). MCD is the rarest form of cutaneous manifestations of CD. This study aims to analyze the clinicohistological features of MCD in a tertiary care center of India. Materials and Methods: A retrospective review of patients diagnosed clinically and histologically with MCD over past 5 years was performed. Data on cutaneous features, histological findings, and response to treatment were collected. Results: Twelve patients (3 men and 9 women) with a mean age of 29 years were identified. All women had vulval involvement in the form of edema (80%), ulceration (60%), and fistula (20%). Among the 3 men, 2 had perineal and scrotal swelling and ulcer, whereas the third patient presented with leg ulcer. Intestinal CD was already diagnosed in 50% patients (5/10) at cutaneous presentation, whereas it was diagnosed subsequently in 30% (3/10) cases. Histological examination revealed nonnecrotizing granulomatous inflammation in the dermis in 11 patients (92%). Additional histological features included eosinophilic infiltrate (58%), panniculitis (33%), and vasculitis (33%). The patients were treated with various combinations of oral prednisolone, metronidazole, minocycline, azathioprine, and subcutaneous adalimumab with partial relief. Conclusion: MCD shows a wide spectrum of clinical presentation, with anogenital involvement being the most common. Histology reveals nonnecrotizing granulomas in the dermis in majority of the cases. The diagnosis is extremely challenging in patients without gastrointestinal involvement at presentation, and thus, a high index of suspicion is imperative.